Let it be, Abbey Road the Beatles - Doggett, Peter 1957- (Schirmer Books [u.a.], 1998)
"The inside story of the recording sessions is brought to life in rare photographs, documenting two of the best-selling rock albums of all time. Also included are critical reviews, a full discography, and a list of bootlegs."--Back cover.
Keywords: Beatles. -- Abbey Road; Beatles. -- Let it be; The Beatles -- Musikgruppe -- Abbey Road; Let it be -- Zusammenstellung, The Beatles, Musikgruppe; Rock music -- History and criticism; Schallplattenaufzeichnung; Geschichte